Mucosal malignant melanoma of nasal cavity presenting in a young male - Mukherjee, Ankur; Rashid, Md Abdur; Dutta, Sirshak; Dutta, Mainak; Saha, Jayanta; Indranil, M; Sinha, Ramanuj (Bangladesh Journal of Otorhinolaryngology, 2011)
Introduction: Mucosal malignant melanoma (MMM) in nose is a rare tumour with an incidence of only 0.67% of all malignant melanomas. It presents more commonly in older age from 5th to 8th decades. Curiously though, in our case, the melanoma presented in a young male with symptoms like a polyp. Case presentation: A 36-year-old male East Indian farmer presented with occasional bleeding from left nasal cavity with nasal obstruction for the last one year with a painless greyish fleshy mass in the left nasal cavity from the past two months. It was initially misdiagnosed as antrochoanal polyp. Endoscopic excision biopsy revealed malignant melanoma. A radical repeat surgical approach was undertaken followed by radiotherapy. Patient is symptom free 6 months following radiotherapy. Conclusion: A high degree of suspicion is necessary to diagnose a malignant melanoma in nasal cavity. It needs a radical curative approach if there is no distant metastasis. Key Words: Mucosa; Melanoma; Nose. DOI: 10.3329/bjo.v17i1.7632 Bangladesh J Otorhinolaryngol 2011; 17(1): 68-71